Effect of cough technique and cryogen gas on temperatures achieved during simulated cryotherapy - Sellors John; Jeronimo Jose; Loesel Charlie; Seamans Yancy; Castle Philip E (BMC, 2007)
Abstract Background Cryotherapy is often used to treat cervical precancer in developing countries. There are different methods and cryogen gases used for cryotherapy, including the freeze-flush-freeze (cough) technique employed to minimize gas blockage. However, there is limited information to compare their effectiveness. Methods Using a tissue model, we compared temperature-time curves for four cryotherapy methods: uninterrupted freezing with nitrous oxide (N2O) and carbon dioxide (CO2), and two methods using a standard and extended version of the cough technique with CO2. Results Uninterrupted freezing with both N2O and CO2 produced tissue temperatures less than -20°C (-40°C and -30°C respectively). CO2 cryotherapy procedures using the two cough techniques produced temperatures greater than -20°C in the model tissue. Conclusion CO2 cryotherapy using the cough technique may not achieve sufficiently low temperatures to produce the desired therapeutic effect. Other alternatives to the prevention of gas blockage should be developed.